A LACANIAN PSYCHOANALYSIS OF THE CHARACTER KARMAN IN AHMAD TOHARI’S KUBAH - Christopher Allen Woodrich (Faculty of Humanities, Universitas Jenderal Soedirman, 2015)
JacquesLacan’s poststructuralist theories of psychology have greatly affected modern understandings of the human psyche. This is evident in literary studies, where numerous thinkers – including Lacan himself – have applied these theories to better understand works of literature. One work which benefits from such an application is Ahmad Tohari’s Kubah, a 1982 novel on the ex-communist Karman’s seeming redemption after spending twelve years as a political prisoner. This paper will use a Lacanian psychoanalysis to show how Karman’s need to find wholeness, one which has been lost since before his birth, led to his various activities, including the joining of the Communist Party and his return to Islam. Although the novel ends on a hopeful note, it will be shown that Karman has not truly found the wholeness for which he has searched.